KOMUNIKASI ANTARPRIBADI PIMPINAN DENGAN KARYAWAN DALAM MENINGKATKAN KINERJA KARYAWAN DI KENTUCKY FRIED CHICKEN (KFC) SUZUYA BINJAI: Sukadamai Gea - Jurnal COMMED (Prodi Ilmu Komunikasi Universitas Putera Batam, 2016)
The process of communication that occurs in the company in particular concerning the of communicationbetween the and employees is an important factor in creating an organization that effective. Communicationeffective determined by the parties involved in which, namely the and employees. The purposes of theresearch were: to understand the process of communication between the leader and the employer inincreasing the performance of work of the employer at Kentucky Fried Chicken (KFC) Company in SuzuyaBinjai. The method of research used in the researh was Qualitatif Descriptive Method. The technique ofcollecting data was by Observing and Interviewing the information from the manager and the dean ofmanager of KFC as the author of the wisdom. The result of this research showed that the process ofinterpersonal communication between the leader and the employer at Kentucky Fried Chicken(KFC)Company in Suzuya Binjai ran well, where the activity was done offensively, with emphaty, supportingaction, positive action and the equal level between the leader and the employer in increasing theperformance of the employer work at KFC Suzuya Binjai. The process of personal communication betweenpersonal ran well, where the manager always explained various important information to them. Besides that,the manager also trained some kinds of training that fuctioned to motivate the employer so that they couldwork better and more profesional.